Results from Colombia's 2014 Report Card on Physical Activity for Children and Youth (2014)
Background: Physical activity (PA) is central to the global agenda for the prevention on noncommunicable diseases (NCDs) Although 80% of NCDs occur in low-To-middle-income countries, the evidence on PA comes mainly from high-income countries In this context, the report card for Colombia is an advocacy tool to help in the translation of evidence into concrete actions The aims of this paper were two-fold: To present the methodology used to develop the first Report Card on Physical Activit in Colombian Children and Youth and to summarize the results. Methods: Twelve indicators of PA were graded using numerica grades (5, highest, to 1, lowest) based on data from national surveys and policy documents. Results: National policy an obesity indicators were graded '4,' while departmental policy and overweight indicators were graded '3.' Overall PA levels sports participation, sedentary behaviors and nongovernment initiatives were graded '2,' and school influence was graded '1. Active transportation, active play, low cardiorespiratory fitness, and family and community influence received an incomplete Conclusion: PA levels are low and sedentary behaviors are high in Colombian children and youth. Although the prevalenc of obesity in Colombia is lower compared with other Latin American countries, it is increasing. A rich legal framework an availability of institutional arrangements provide unique opportunities to bridge the gap between knowledge and practice tha need to be evaluated. © 2014 Human Kinetics, Inc.